DEVELOPMENT OF RABBIT GOALS GAME TO INCREASE STUDENT MOTIVATION IN THEMATIC LEARNING AT PRIMARY SCHOOL - Uswatun Hasanah (Jurnal Teknoinfo, 2023)
Playing is an activity that cannot be separated in children lives. Children preference for playing needs attention so that the games they do support their competence. Especially with the development of technology in the era of the Industrial Revolution 4.0, it has changed the pattern of conventional games into digital-based games. So it is necessary to develop educational games that can meet the needs of children in playing and learning. The purpose of this study was to develop an educational game for thematic subjects called rabbit goals and to find out the impact of using this game on children learning motivation. This research was conducted at MI Barokah At-Tahdzib for 2nd grade students. The results of this development are in the form of a game that contains thematic material and displays for 2nd grade students. The impact of using this educational game includes increasing student motivation, increasing student accuracy, improve students ability in arithmetic operations, and build independent learning in students, because according to students learning by using rabbits is the goal to be more exciting and fun.